Samuel Hildebrandt – Ekaterina E. Kozlova (eds.), Loneliness in the Hebrew Bible (Library of Hebrew Bible/Old Testament Studies 718; London: T&T Clark 2025) - Zieliński, Marcin (The Biblical Annals, 2026)
Book review: Samuel Hildebrandt – Ekaterina E. Kozlova (eds.), Loneliness in the Hebrew Bible (The Library of Hebrew Bible/Old Testament Studies 718; London: Clark 2025) Pp. 248. £ 64.60 (E-Book); £ 108 (Hardback). ISBN: 978-05- 67-71445-9 (E-Book); 978-05-67071444-2 (Hardback).